DEVELOPMENT OF ETHNOMATHEMATICS-BASED STUDENT WORKSHEETS ON THE ORNAMENTS OF MAIMUN PALACE IN MEDAN - Nasution, Sarmila Fitri Yanti; Lubis, Mara Samin (JME (Journal of Mathematics Education), 2025)
This study aims to develop valid, practical, and effective ethnomathematics-based worksheets using the ornaments of Maimun Palace in Medan for Grade IX students of SMP Sinar Husni in the 2024/2025 academic year. This research uses the Research and Development (RD) development model of the ADDIE model which includes Analysis, Design, Development, Implementation, and Evaluation. The research subjects were 22 students of class IX-2 SMP Sinar Husni. Validation results indicate high validity indices from material (0.82), media (0.82), and language experts (0.83). Teachers and students rated the worksheets as very good and practical, with average scores of 3.7 and 3.33 out of 4.00 respectively. Student responses fall into the 'very strong' category, with a score of 83.31%. Effectiveness is seen from classical learning completeness of 86.37% and an increase in learning outcomes of 59.37%. The average N-gain value is 0.53 (medium category). Therefore, the developed ethnomathematics-based worksheets can serve as innovative and effective alternative teaching materials to improve students’ learning outcomes.